Answer:
A.) Even.
Step-by-step explanation:
If a function is an even function, then
F(-x) = f(x)
Also, if a function is an odd function, then, f(-x) = -f(x)
You are given the below function
f(x) = 1 + 3x^2 − x^4
Let x = 2
Substitute 2 for x in the function
F(x) = 1 + 3(2)^2 - (2)^4
F(x) = 1 + 3(4) - 16
F(x) = 1 + 12 - 16
F(x) = -3
Also, Substitute -2 for x in the function
F(x) = 1 + 3(-2)^2 - (-2)^4
F(x) = 1 + 3(4) - 16
F(x) = 1 + 12 - 16
F(x) = -3
Since f(-x) = f(x), we can conclude that
F(x) = 1 + 3x^2 - x^4 is even
Answer:
The discount is $18
Step-by-step explanation:
Answer:
Step-by-step explanation:
<h2>A rocket is launched from a tower. The height of the rocket, y in feet, is related to the time after launch, x in seconds, by the given equation. Using this equation, find the time that the rocket will hit the ground, to the nearest 100th of second.
</h2><h2>y=-16x^2+129x+119
</h2><h2>y=−16x </h2><h2>2
</h2>
+129x+119
Answer:
50% or 1/2 Could be 100% but i think it is 50%
Step-by-step explanation:
Because Changing the coin will make no difference.